2020
DOI: 10.1038/s41418-020-0520-5
|View full text |Cite
|
Sign up to set email alerts
|

HPV-mediated nuclear export of HP1γ drives cervical tumorigenesis by downregulation of p53

Abstract: E6 oncoprotein derived from high-risk human papillomavirus (HPV) drives the development of cervical cancer through p53 degradation. Because cervical cancer therapies to inactivate HPV or E6 protein are not available, alternative strategies are required. Here, we show that HPV-mediated nuclear export of human heterochromatin protein 1γ (HP1γ) reduces the stability of p53 through UBE2L3-mediated p53 polyubiquitination during cervical cancer progression. In general, HP1 plays a key role in heterochromatin formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 57 publications
(76 reference statements)
3
27
0
Order By: Relevance
“…Previously, we found a way to block the cervical cancer-specific p53 degradation by inducing HP1γ-mediated suppression of UBE2L3 [15]. Moreover, we revealed that E6 promoted cytoplasmic diffusion of HP1γ, disturbing the epigenetic silencing of UBE2L3 [15]. In the current study, we further demonstrate a pharmacological strategy targeting these mechanisms to resolve cisplatin resistance in cervical cancer cells.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Previously, we found a way to block the cervical cancer-specific p53 degradation by inducing HP1γ-mediated suppression of UBE2L3 [15]. Moreover, we revealed that E6 promoted cytoplasmic diffusion of HP1γ, disturbing the epigenetic silencing of UBE2L3 [15]. In the current study, we further demonstrate a pharmacological strategy targeting these mechanisms to resolve cisplatin resistance in cervical cancer cells.…”
Section: Discussionsupporting
confidence: 66%
“…The E6 protein derived from high-risk HPV stimulates poly-ubiquitination of p53 by E6AP (E3 ligase) and UBE2L3 (E2) [11,12]. Previously, we found a way to block the cervical cancer-specific p53 degradation by inducing HP1γ-mediated suppression of UBE2L3 [15]. Moreover, we revealed that E6 promoted cytoplasmic diffusion of HP1γ, disturbing the epigenetic silencing of UBE2L3 [15].…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations